Pengaruh Nilai Kearifan Lokal, Kepribadian, dan Budaya Kerja Terhadap Motivasi Pelayanan Publik PNS - Vivioli A, Annisa (LPPM Universitas Ekasakti, 2021)
This study aims to assess the impact of local knowledge, personality traits, and work environment on the motivation levels of civil servants working in public service in Bukittinggi City. This study employs quantitative methodologies, utilizing exogenous variables, specifically local wisdom value variables (X1), personality (X2), work culture variables (X3), and endogenous variables, notably public service motivation (Y). The research population comprised 41 personnel from the Population and Civil Registration Service of Bukittinggi City. The sample was obtained using complete sampling, with a standard error of 5%. This means that all 41 respondents in this survey represent the entire population. The employed data analysis technique is descriptive analysis. The data was gathered using questionnaires that had undergone prior validation and demonstrated reliability, both in content and empirical testing of the items in the field. The research findings indicate that the value of local wisdom significantly impacts the motivation of civil servants in the Bukittinggi City Population and Civil Registry Service to engage in public service. Their personality influences the motivation for public service of civil workers in the Bukittinggi City Population and Civil Registry Service. The motivation for civil officials to serve in public in Bukittinggi City Population and Civil Registry Service is influenced by work culture. The motivation for public service of civil officials in the Bukittinggi City Population and Civil Registry Service is influenced by the concurrent impact of local wisdom, personality, and work culture.